Towards an analytical model of a pin-lug connection. (15th October 2022) - Strozzi, Antonio; Giacopini, Matteo; Bertocchi, Enrico; Mantovani, Sara; Baldini, Andrea
Highlights: Analytical modelling of pin-lug progressive contact. Curved beam model of the lug solved by Castigliano's theorem. Definition of enhanced load factor accounting for initial clearance and lug geometry. Contact extent evaluation in terms of load factor. Comparison between numerical and analytical forecasts. Abstract: A preliminary analytical model of a pinned connection is carried out. The lug is idealized in terms of a curved beam, and the presence of an initial clearance between the pin and the lug is accounted for. This model rationalizes the nonlinear and linear mechanical responses of the structure; a coefficient summarizing the effect of the load, Young's modulus, and initial clearance, is derived; this coefficient is kindred to that computed according to the theory of elasticity. An enhanced load factor that accounts for the lug geometry is proposed. Two loci of local maximum stress occur. One point is the stress at the centre of the pin-lug contact, whereas the other point falls laterally along the lug bore border. While the central stress is forecast by the analytical model with reasonable accuracy, the analytical stress computed laterally is too approximate to be employed in engineering applications. Despite this drawback, a better understanding of the load transfer mechanism within the pinned connection is achieved, by particularly rationalizing the nonlinear, progressive character of the pin-lug contact, and the usefulness of the load factor.